The effects of barley particle size on finishing-pig performance - Goodband, Robert D.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials utilizing 280 finishing pigs were conducted to evaluate the effects of barley particle size on finishing-pig performance. In Experiment 1, pigs fed barley ground through a hammermill with a 1/8-in screen were not different in average daily gain (ADG) or feed efficiency (F/G) from pigs fed a milo-based diet ground through a 3/16-in screen. Pigs fed either 3/16 or 1/4-in ground barley grew slower and were less efficient (P<.02) than those fed either the milo or finely ground barley diet. Experiment 2 was conducted in a similar manner, with the exception that mill run barley was used instead of a specific variety. In Experiment 2, ADG and average daily feed intake (ADFI) were not different between dietary treatments. This response resulted in a trial x treatment interaction for these criteria. Results for feed efficiency were similar to those in Experiment 1; pigs fed 3/16 or 1/4-in ground barley diets were less efficient (P<.02) than those fed l/8-in ground barley or 3/16-in ground milo. These results suggest that the variety of barley is an important criteria in determining feeding value for finishing-pigs, and that reducing particle size of the diet by fine grinding improves feed efficiency.
Keywords: Swine; Barley; Finishing pig performance